Islamic Acculturation and Local Culture on Nyiramkeun Tradition in Talagawetan Village Majalengka Regency - Ali Syamsuddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research tries to explain the acculturation between Islam and Sundanese culture in the Nyiramkeun tradition. The problems raised in this study are the origin, procession, or implementation of the Nyiramkeun ritual tradition, the form of acculturation between Sundanese and Islamic culture, the meaning or the perceptions of the Talagawetan villagers on the influence of tradition on their lives. This research was field research, according to the theory of acculturation according to Koentjaraningrat. In essence, field research aims to find out the specifics and realities of what happens in society. The anthropological approach used in this research is ethical and emic theory. With data collection techniques used are observation, interviews, and documentation. The research results can be seen from several things, namely, first, the Nyiramkeun ceremony tradition in the village of Talagawetan has existed around the 1820s, namely since the Talaga Manggung government was transferred to Sindangkasih. Second, the acculturation process in the Nyiramkeun ceremony tradition, namely the prayer's recitation. The do'a uses do'a-do'a in Arabic acculturated with the Sundanese language, which is combined in the prayer, where the prayer in the Sundanese language is known as Hadoroh. In addition to the acculturation prayer between Sundanese and Islamic cultures, namely the staging of traditional arts such as karinding, sada awi, debus, gembyung, and jaipong, know that these arts do not originate from Islamic culture but are acculturation between Hindu-Buddhist culture and culture. Islam. The three public perceptions of Islamic acculturation can give the meaning that this Nyiramkeun Traditional Ceremony is an activity to carry out and preserve the heritage of the Talaga Manggung Kingdom, to purify oneself, and as a suggestion to strengthen the ties of brotherhood between descendants of the Talaga Manggung kingdom and members of the community in Talagawetan Village. Generally, as well as maintaining the preservation of the surrounding natural environment. The community has accepted the tradition of the Nyiramkeun ceremony. However, this ceremony tradition was far from Islamic elements, and gradually this tradition has merged with Islamic teachings.